(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2020)
Apart from artificial intelligence’s (AI) impressive abilities, it cannot avoid errors in judgment. This article intends to explain the weaknesses of the law of tort in addressing the threats of AI. This article also discusses the development of AI in Malaysia in order to assess Malaysia’s readiness to face the legal threats caused by AI. The research methodology employed for this article is qualitative in nature. The data referred to in this article is based on the law of tort, previous cases decided by the courts, articles in journals, and online resources. The analysis of the available data concludes that AI has brought about new forms of threats in the realm of the law of tort. At this time, Malaysia has yet to have any legal preparation to face threats from AI. If these weaknesses are left unaddressed, tort victims may face difficulties in future to claim damages against the tortfeasor. Keywords: artificial intelligence, AI, tort, threats, legal personality